Impact of IITA cassava varieties in Oyo State, Nigeria, 19761985 - Akoroda, M.O.; Gebremeskel, T.; Oyinlola, A. (1989)
Cassava improvement research at the International Institute of Tropical Agriculture (I1TA) developed several new varieties during 1976-1985 that entered into the cassava culture of Oyo State of Nigeria where IITA is situated. The focus of this study was to determine the level of overall impact of IITA varieties on cassava cultivation and contribution to food and income of rural farm families in the state based on field travels discussions with farmers. Data from questionnaires completed by TUfal extension agents of the Oyo State Ministry of Agriculture. And from individual farmers and knowledgeable local residents. we conclude that (i) UTA cassava varieties have been adopted by big and small farmers and cover at least some 30,000 ha or one fifth of Oyo State's cassava hectare cultivated to 40-50 cassava varieties; (ii) areas of adoption (after about seven years of tenuous multiplication of plantable stems) largely coincided with localities that received an initial supply of plantable stem cuttings; (iii) IITA cassava varieties contribute about 16% of the home food of rural farm families and 13-26% of their annual farm income; and (iv) about a 3•fold annual increase in adoption (mainly variety replacement) can be expected if plantable stems supply is adequate.